2020
DOI: 10.1002/ar.24502
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary adaptations in the flexor digitorum profundus muscle in Tamandua mexicana (Xenarthra, Myrmecophagidae)

Abstract: The northern tamandua (Tamandua mexicana) is a neotropical mammal of the order Pilosa, suborder Vermilingua, and family Myrmecophagidae. This species has anatomical and functional adaptations in its forelimb for semiarboreal quadrupedal locomotion. Several studies have reported that the medial head of the triceps brachii and flexor digitorum profundus muscles are fused in species belonging to the family Myrmecophagidae. However, there is no reference to the innervation in these. The triceps brachii muscle is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 45 publications
(74 reference statements)
0
11
0
Order By: Relevance
“…Thus, the aim of this study was to perform a detailed description of the FDS, IF and PL muscles of P. flavus and P. cancrivorus , reviewing their characteristics such as origin, insertion, innervation and arterial supply and to report differences that have not been described by several authors in P. flavus (Beswick‐Perrin, 1871; Julitz, 1909; Taverne et al., 2018; Böhmer et al., 2019, 2020) and P. cancrivorus (Windle, 1888; Lima et al., 2010; Santos, Bertassoli, Rosa, et al., 2010). This study also carried out a comparative study with those reported on other carnivores and primates to review the most appropriate terminology of these muscles according to their attachments, functionality and innervation, as recommended by several authors (Diogo & Abdala, 2010; Diogo & Wood, 2012; Kawashima et al., 2017; Vélez‐García et al., 2020). In carnivores, it is very common to find reports with several names for the same muscles; for example, the FDS is named as PL or the IF as FDS.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the aim of this study was to perform a detailed description of the FDS, IF and PL muscles of P. flavus and P. cancrivorus , reviewing their characteristics such as origin, insertion, innervation and arterial supply and to report differences that have not been described by several authors in P. flavus (Beswick‐Perrin, 1871; Julitz, 1909; Taverne et al., 2018; Böhmer et al., 2019, 2020) and P. cancrivorus (Windle, 1888; Lima et al., 2010; Santos, Bertassoli, Rosa, et al., 2010). This study also carried out a comparative study with those reported on other carnivores and primates to review the most appropriate terminology of these muscles according to their attachments, functionality and innervation, as recommended by several authors (Diogo & Abdala, 2010; Diogo & Wood, 2012; Kawashima et al., 2017; Vélez‐García et al., 2020). In carnivores, it is very common to find reports with several names for the same muscles; for example, the FDS is named as PL or the IF as FDS.…”
Section: Introductionmentioning
confidence: 99%
“…The m. anconeus medialis is similar in several species of Xenarthra (Galton, 1869;Humphry, 1869;Macalister, 1875b;Pereira et al, 2021;Rapp, 1852;Taylor, 1978;Vélez-García et al, 2021;Windle & Parsons, 1899). However, in B. variegatus, this muscle is a head of m. triceps brachii (accessory anconeus) (Olson et al, 2018).…”
Section: Comparative Myology Within the Superorder Xenarthramentioning
confidence: 93%
“…Some anatomical studies in Xenarthrans present a functional analysis of the thoracic limb muscles (Amson & Nyakatura, 2018;Nyakatura & Fischer, 2011;Olson et al, 2016Olson et al, , 2018Polania-Guzm an & Vélez-García, 2019;Taylor, 1978;Toledo et al, 2013;Vélez-García et al, 2021). In order to perform such an analysis, it is necessary to take the muscle mass of the thoracic limbs into consideration (Polania-Guzm an & Vélez-García, 2019;Souza-Junior et al, 2021) that is a key variable for analyzing muscle strength by means of the physiologic cross-sectional area (Olson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations